DIGITAL-BASED PROMOTION STRATEGY FOR INCREASING TOURISTS' INTEREST IN VISITING THE GLUGUR RIMBUN LIVESTOCK FARMING AREA - Lubis, Hidayati Purnama; Franita, Riska; Siswoyo, Purwo; Rahayu, Putri Suci (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The purpose of this research is to find out the right promotional strategy for introducing new tourist attractions to generate interest in visiting tourists to the Livestock Area of the Al Amin Science and Industrial Park (Living Lab) Glugur Rimbun Village Sampe Cita Kutalimbaru District Deli Serdang Regency. The research approach uses descriptive qualitative methods, namely literature study research methods sourced from previous research publications related to the title. The results of this study explain that the use of social media is the most dominant means of communication with consumers in the selection of digital-based promotional strategies.